(untitled) (Marketing Journal, 2026)
Abstract This article evaluated the competitiveness of industrial enterprises in the Surkhandarya region using economic and statistical methods. The study analyzed the volume of industrial production, development dynamics, and the region’s share in the total industrial output of the country. Competitiveness was assessed using the industrial production index, labor productivity index, and an integrated competitiveness index. Statistical data for the period 2014-2024 were examined to identify growth rates and structural characteristics of regional industry. The analysis showed steady growth of industrial production in absolute terms, while the share of the region in national industrial output remained relatively low. The results indicated the need for industrial diversification, development of innovative production activities, and improvement of labor productivity to strengthen regional industrial competitiveness. Keywords: Surkhandarya region, industrial enterprises, competitiveness, industrial production, labor productivity, integrated index, economic and statistical analysis.